Evolutionary Genomics Reveals Multiple Functions of Arylalkylamine N-Acetyltransferase in Fish - Huang, Yu; Li, Jia; Bian, Chao; Li, Ruihan; You, Xinxin; Shi, Qiong (Frontiers in Genetics, 2022)
As an important hormone, melatonin participates in endocrine regulation of diverse functions in vertebrates. Its biosynthesis is catalyzed by four cascaded enzymes, among them arylalkylamine N-acetyltransferase (AANAT) is the most critical one. Although only single aanat gene has been identified in most groups of vertebrates, researchers including us have determined that fish have the most diversity of aanat genes (aanat1a, aanat1b and aanat2), playing various potential roles such as seasonal migration, amphibious aerial vision, and cave or deep-sea adaptation. With the rapid development of genome and transcriptome sequencing, more and more putative sequences of fish aanat genes are going to be available. Related phylogeny and functional investigations will enrich our understanding of AANAT functions in various fish species.